Self-sovereign identity - Alexandra Giannopoulou; Fennie Wang (Internet Policy Review)
The concept of self-sovereign identity (SSI) describes an identity management system created to operate independently of third-party public or private actors, based on decentralised technological architectures, and designed to prioritise user security, privacy, individual autonomy and self-empowerment.